UNFPA state of World population 2004 - United Nations Population Fund (New York, 2004)
The World Energy Assessment report released in 2000 (ISBN 9211261260) considered energy policy options and challenges in the context of sustainable development objectives, and analysed trends based on data analysis available in 1998. This publication updates this analysis, taking into account developments and information available through to early 2003. Topics covered include: the discussions at the World Summit for Sustainable Development, held in Johannesburg in 2002; energy linkages to major global issues such as access to affordable energy services, poverty alleviation, economic development, greenhouse gas emissions, fuel supply and security; energy resources and technological options; using energy scenarios to gauge whether sustainable futures are possible; and identification of key energy policies and strategies to achieve sustainable economic growth.
Keywords: Population-World